Development and antioxidant evaluation of mango leaf (Mangifera indica L.) extract loaded silk fibroin nanoparticles - Phuong, Nguyen Thi Ngoc; Ha, My Tien; Nguyen, Doan Xuan Tien; Nguyen, Ngoc Yen; Huynh, Huynh Anh Thi; Hau, Trieu Phu; Quyen, Tran Thi Bich; Nguyen, Manh Quan; Nguyen, Anh Tuan; Pham, Duy Toan (Frontiers in Materials, 2024)
The main antioxidant polyphenol compounds in the mango (Mangifera indica L.) leaf extract are susceptible to environmental degradations. Thus, in biomedical applications, the mango leaf extract is commonly encapsulated in a carrier. However, most studies employed the synthetic carrier materials that could affect the human health, and the complicated formulation procedure that could hinder the scalability. Therefore, this work, for the first time, explored the use of silk fibroin (an FDA-approved biomaterial), in nanoparticles platform, to encapsulate and deliver the mango leaf extract, utilizing the simple coacervation preparation method. Initially, the mango leaf ethanolic extract was obtained through maceration, resulting in a total phenolic content of 76.39 ± 0.14 mg GAE/g DPW and a notably high antioxidant activity (IC50 = 6.872 ± 0.512 µg/mL). Subsequently, silk fibroin nanoparticles loaded with the extract were developed by the coacervation technique. Depending on the fibroin content, these nanoparticles exhibited an appropriate size range of 500–800 nm with narrow size distributions, a spherical shape with smooth surfaces, a dominant silk-II crystalline structure, a drug entrapment efficiency exceeding 70%, and retained the main biomarker mangiferin. Moreover, the phenolic-compounds release profiles from the particles followed the three-step process, the first burst-release step, the second sustained-release step, and the third degradation step. The particles were also non-toxic to the erythrocytes and the human embryonic kidney HEK-293 cell line. Lastly, the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay demonstrated that the antioxidant activity of the mango leaf extract was preserved within the extract-loaded nanoparticles. The results suggested that the silk fibroin nanoparticles could be a potential platform to effectively encapsulate and deliver the mango leaf extract for biomedical purposes.